Factors Related to Nutritional Status of Toddlers in the Working Area of Soropia Health Center, Konawe Regency in 2021 - Lisnawaty; Jafriati; Nurfajriyanti Hamka; Febriana Muchtar (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2022)
Background: Nutritional status is a state of health related to the use of food by the body. As a result of poor nutritional status during infancy, it can cause stunted growth, cause toddlers to be lazy to carry out activities related to energy production, disruption of the toddler's immune system so that they are susceptible to infectious diseases, inhibition of optimal brain growth, and changes in behavior such as apathy. Purposes: This study aimed to determine the relationship between parental income, and eating patterns in children under five with the occurrence of malnutrition in children under five in the working area of ​​Soropia Health Center. Methods: This research was a quantitative research that is observational analytic with a Cross Sectional Study approach. The number of samples were 50 toddler with a sampling technique using total sampling and for analysis using the Chi-Square test. Results: The results showed that there was a relationship between parental income (p=0.048) and eating patterns (p=0.000) with the nutritional status of children under five in the Soropia Health Center area in 2021. Conclusion:it was found that there was a relationship between parents' income and diet. on the nutritional status of children.